THE SYNCHRONIZATION NECESSARY OF NOTARY SUPERVISION BY NOTARY SUPERVISORY AND HONOUR COUNCIL - Suwardi Suwardi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
In line with the Notary's accountability for his authority, and compliance with that authority, legal certainty must be guaranteed with a continuous and effective supervision and guidance. There are currently two notary supervision and guidance institutions in Indonesia, namely the Notary Supervisory Council and the Notary Honorary Council. This study uses a normative juridical approach, which is a research that is focused on examining the application of norms or norms in positive law. Article 67 paragraph (2) of Act No. 2 of 2014 states that the Notary Supervisory Council shall supervise notaries including the behavior of the notary and the implementation of office by the notary. Meanwhile, the Honorary Council itself only provides guidance and supervision to the extent that it violates ethics. What must be remembered is that the authority possessed by the Notary Supervisory Council looks so 'broad'. This is because the Notary Supervisory Council is not only authorized to carry out guidance and supervision of notaries who violate the provisions of the law. However, the Notary Supervisory Council also provides guidance and supervision of ethical violations as carried out by the Honorary Council. The conclution of this reseach is Synchronization of Notary Supervision by the Notary Supervisory Council and guidance by the Notary Honorary Council in law enforcement is very necessary.